Motivations and experiences related to women's first same-sex sexual encounters. Issue 1 (3rd April 2017) - Talley, Amelia E.; Cook, Mackenzie A.; Schroy, Catherine A.
ABSTRACT: Using women's self-identified sexual identity, the current study compares motivations for first same-sex sexual encounters as well as associated experiential outcomes. We also examine whether relations between sexual motivations and experiential outcomes differ as a function of women's sexual identity status. Participants were women ( N = 123), ages 18–29 ( M = 21.59, SD = 3.33), who self-reported a history of same-sex sexual contact. Approximately 27% of women identified as exclusively heterosexual (i.e. EH), 35% as primarily heterosexual (i.e. 'mostly heterosexual' [MH]), and 38% as exclusively or primarily lesbian/gay, or bisexual (i.e. LGB). Participants completed an online survey. MH and LGB women reported first same-sex sexual encounters that were more motivated by intimacy and exploration motives, relative to EH women. Compared to MH and LGB women, EH also engaged in fewer sexual activities with their first same-sex partner. Intimacy and exploration motives were related to positive experiential outcomes during first same-sex contact. Associations between motivations and experiential outcomes were not moderated by sexual identity. Findings contribute to understanding motivations and experiences related to women's first same-sex sexual encounters and show that not all women with a history of same-sex sexual contact subsequently identify with a minority sexual identity label.